EVENT INDUSTRY: IMPACT, CHALLENGES AND EVOLVEMENT IN POST PANDEMIC ERA - Zakirai@Zakaria, Norlida; Nor Azam, Noor Haty; Bashirun, Siti Norashikin; Mohd Kodri, Aida Nur; Jislan, Fatanah (Jurnal ’Ulwan, 2022)
COVID-19 has had an impact on almost every aspect of life. The events industry was, predictably, one of the worst affected by the pandemic. Therefore, this review paper intends to explore the impacts, challenges and evolvement of the event management industry by reviewing the available literature. This study indicates that the pandemic situation significantly has effects on economic activities, events workforce, and organizers. In addition, there are also some challenges of COVID-19 such as the emergence of the online event management system and the need to upskill the event workforce. This review then highlights the event theory that supports the evolution of the industry after the pandemic era. It appears that events activities arising with the implementation of virtual and hybrid events. Future research on the event industry should be undertaken to assess recovery strategies by other hospitality industries as a benchmarking approach.